Polyphenols as Antitumor Agents Targeting Key Players in Cancer-Driving Signaling Pathways - Cháirez-Ramírez, Manuel Humberto; de la Cruz-López, Karen Griselda; García-Carrancá, Alejandro (Frontiers in Pharmacology, 2021)
Polyphenols constitute an important group of natural products that are traditionally associated with a wide range of bioactivities. These are usually found in low concentrations in natural products and are now available in nutraceuticals or dietary supplements. A group of polyphenols that include apigenin, quercetin, curcumin, resveratrol, EGCG, and kaempferol have been shown to regulate signaling pathways that are central for cancer development, progression, and metastasis. Here, we describe novel mechanistic insights on the effect of this group of polyphenols on key elements of the signaling pathways impacting cancer. We describe the protein modifications induced by these polyphenols and their effect on the central elements of several signaling pathways including PI3K, Akt, mTOR, RAS, and MAPK and particularly those affecting the tumor suppressor p53 protein. Modifications of p53 induced by these polyphenols regulate p53 gene expression and protein levels and posttranslational modifications such as phosphorylation, acetylation, and ubiquitination that influence stability, subcellular location, activation of new transcriptional targets, and the role of p53 in response to DNA damage, apoptosis control, cell- cycle regulation, senescence, and cell fate. Thus, deep understanding of the effects that polyphenols have on these key players in cancer-driving signaling pathways will certainly lead to better designed targeted therapies, with less toxicity for cancer treatment. The scope of this review centers on the regulation of key elements of cancer signaling pathways by the most studied polyphenols and highlights the importance of a profound understanding of these regulations in order to improve cancer treatment and control with natural products.